SISTEM INFORMASI PENGELOLAAN DATA PENDUDUK (STUDI KASUS: RT/RW KELURAHAN PONDOK KACANG TIMUR) - Wisti Dwi Septiani (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2018)
Currently, work in every institution whether government or private institutions are involved in the management of population data. Including the management of population at the Hamlet level and Neighbourhood. The current problem in Pondok Kacang Timur is the lack of organizational data archiving of the population, many data is still handwritten and stored in the master book. The process of submitting a letter takes a long time because it must match the data with the files in the archive. In addition, some archives scattered and disappeared with the migration of office stewardship in every assignment period. Utilization of ICT advancement needs to be applied in order to simplify the problems encountered in the management of the population. Solutions for solving an existing problem by using the waterfall method with designing desktop based application to the management of population data. The result of this desktop based application is to facilitate the storage of data with the database, making of the report more effective and efficient.